Over 10% efficiency in single-junction polymer solar cells developed from easily accessible random terpolymers. (September 2017) - Cho, Hye Jin; Kim, Yu Jin; Chen, Shanshan; Lee, Jungho; Shin, Tae Joo; Park, Chan Eon; Yang, Changduk
Abstract: Despite the numerous random polymers recently developed for polymer solar cells (PSCs), very limited attention has been directed toward controlling the ratio of widely used thiophene (T) to bithiophene (2T) chromophores in their backbones. Herein, we developed a new family of thieno[2ʹ, 3ʹ:5ʹ, 6ʹ]pyrido[3, 4- g ]thieno[3, 2- c ]isoquinoline-5, 11(4 H, 10 H )-dione-based random terpolymers containing different T and 2T compositions. In-depth structure–property investigations covering physical properties, morphology, and PSC performance with respect to T:2T in the polymers were performed by several structural characterization techniques. Over a range of compositions, these random terpolymers provide impressive fill factor (FF) as well as short-circuit current density ( J SC ) values far higher than that of the alternating parent polymer. Especially, the PSC based on a terpolymer with the optimized T:2T value of 7:3 shows quite higher J SC of 18.3 mA cm −2 and FF of 71.2%, leading to a highly superior power-conversion efficiency (PCE) of 10.8%. Because of the drastic boost in PCEs provided by simply tuning T:2T in the backbones, our discovery finds use in fully exploiting the potential of various material systems and raises the hope of achieving even higher PCEs, thereby competing with other photovoltaic technologies. Graphical abstract: Highlights: High efficiency of 10.8% in polymer solar cells is achieved using TPTI-random terpolymers. Simply tuning composition in random backbones plays a critical role in device performances. Easily accessible TPTI-T random terpolymers are highly desirable for real solar cell applications.